Microbiology and Clinical Characteristics of Industrial Oil Burns. (4th October 2017) - Kelly, Devin; Rizzo, Julie; Yun, Heather; Blyth, Dana
Abstract: Background: Injured oil workers are exposed to a broad microbiome in hydraulic fracturing fluids (HFF) and oil wells at the time of injury. This includes Pseudomonas, Stenotrophomonas, Acinetobacter, and rare human pathogens which may be harder to culture. This study evaluates oil-related burn (ORB) microbiology. Methods: Patients admitted to the USAISR burn center enrolled in the Epidemiology of Workplace Burns and Injuries in Texas registry from April 2011 to November 2016 were included as cases and controls. Patients hospitalized ≤2 days were excluded. ORB was defined as exposure to HFF (FORB), or non-HFF (NFORB). Controls were patients admitted with industrial burns (non-ORB). Patient demographics and clinical cultures (days 1–15) were obtained through the registry and electronic medical record. Results: 149 industrial burns were included, of which 35 (23%) were ORB and 114 (77%) were non-ORB. Of the ORB, 11 (31%) were FORB and 24 (69%) were NFORB. ORB had a median age, TBSA, and Baux score of 31, 25, and 58 compared with non-ORB with 36, 4, and 44, respectively ( P < 0.01). Twenty-five patients had positive cultures: 12 (48%) non-ORB and 13 (52%) ORB. Sixty Isolates identified from the ORB population included Flavobacterium, Pseudomonas, and Serratia. FORB accounted for three (25%) of the culture positive ORB. S. marcescens was isolated in 1 FORB (33%) compared with 0 NFORB and non-ORB ( P < 0.05). Otherwise, there was no statistical difference in isolates. Median time to first positive culture differed among non-ORB (4 days), FORB (13 days), and NFORB (3.5 days, P  = 0.03). Forty-six (31%) patients had cultures obtained during admission: three (7%) FORB, 12 (26%) NFORB, and 31 (67%) non-ORB. Of cultured patients, ORB had a median TBSA and Baux score of 44 and 90 compared with non-ORB with 11 and 47, respectively ( P < 0.01). Comparing all cultured patients, ORB had more positive, negative, and total cultures compared with non-ORB with 2 vs. 0, 7 vs. 3, and 10 vs. 3, respectively ( P <  0.01). Conclusion: Within this cohort, ORB was associated with more severe injuries compared with non-ORB. They had more positive, negative, and total cultures, and recovery of S. marcescens was associated with FORB. Larger studies with non-culture based technology could help further define the microbiology of this uniquely exposed population. Disclosures: All authors: No reported disclosures.